Antioxidant Capacity of Anthocyanins and other Vegetal Pigments: Modern Assisted Extraction Methods and Analysis - Asuero, Agustín G.; Tena, Noelia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint contains thirteen contributions on recent advances in the field of anthocyanins and other vegetal pigments and state-of-the-art extraction methods applied to different matrices. The interdisciplinary character of the subject and the breadth of the contents presented by the authors make this book very interesting and comprehensive. This reprint covers different topics such as the most modern and cutting-edge methods for the analysis and extraction of anthocyanins, their geographical variability, the improvement and protection of their antioxidant properties, the valorization of by-products, stability studies and the metabolomics of chlorophylls and carotenoids, all of which are the subject of research and review in this reprint.